The Effect of Perceived Organizational Support and Job Satisfaction on Employees Performance of Administration and Finance Department at Kebon Agung Sugar Factory Malang through Organizational Commitment as an Intervening Variable - Krisna Febriantoro; Lohana Juariyah (Ekonomi Bisnis, 2018)
ABSTRACTFebriantoro, Krisna. 2018. The Effect of Perceived Organizational Support and Job Satisfaction on Employees Performance of Administration and Finance Department at Kebon Agung Sugar Factory Malang through Organizational Commitment. Sarjana’s Thesis, Department of Management, Faculty of Economics, Universitas Negeri Malang. Advisor: Lohana Juariyah, S.E., M.SiKeywords: Perceived Organizational Support, Job Satisfaction, Organizational Commitment, PerformanceHuman Resources is one of the most important resources for the establishment of a company. Therefore, the ability to manage the performance of human resources appropriately is determine the ability to achieve success in achieving goals and establish the ability to deal with threats to companies both internal and external. Important factors that employees must possess to making high employee performance include the perceived organizational support, job satisfaction, and organizational commitment.This study purpose to know : (1) Condition of perceived organizational support, job satisfaction, organizational commitment and employee performance. (2) The direct influence of perceived organizational support on employee performance. (3) The direct influence of perceived organizational support on organizational commitment. (4) The direct influence of organizational commitment on employee performance. (5) The direct influence of job satisfaction on employee performance. (6) The direct influence of job satisfaction on organizational commitment. (7) Indirect influence of perceived organizational support on employee performance through organizational commitment. (8) Indirect influence of job satisfaction on employee performance through organizational commitment.The study uses cuantitive approach, the population is the administrative and financial employees of Kebon Agung Sugar Factory Malang which has status as permanent employee with the total sample as much as 68 respondents from 68 employees. The method to taking sampling is by total sampling method and instrument testing technique using validity and reliability test. This study uses several models of classical assumption test is normality test, multicolliniearity test, and heteroskidasticity test. Data analysis method used is path analysis.Based on the results of the analysis is showed that: (1) Description of perceived organizational support, job satisfaction, organizational commitment and employee performance is good. (2) There is a positive influence and significant perceived organizational support on employee performance. (3) There is a positive influence and significant perceived organizational support on organizational commitment. (4) There is positive influence and significant organizational commitment on employee performance. (5) There is a positive influence and significant job satisfaction on employee performance. (6) There is a positive influence and significant job satisfaction on organizational commitment. (7) There is a positive and indirectly significant effect of perceived organizational support on employee performance through organizational commitment. (8) There is a positive and indirect effect of job satisfaction on employee performance through organizational commitment.Based on the results of this study, researchers suggest: (1) Companies need to maintain awareness of the welfare of employees and also need to improve preparedness of the company if the employee needs special help. Other than that the companies need to keep the working conditions of the company in order to stay comfortable and need to increase the chances of employees participating in decision making within the working group. The next suggestion is, that company needs to keep employees to remain happy career in the company either by increasing organizational support and employee satisfaction and also need to pay attention to the employee's view that someone is easy to move company either by paying attention to opinion and value from employee. In addition, companies need to maintain and manage employees in order to remain able to cooperate well with colleagues and also need to improve the accuracy of employees in running the job either by increasing supervision or provide punishment or punishment to employees. (2) Next research on the effect of perceived organizational support variables, job satisfaction, and organizational commitment to employee performance suggests that the analysis model used is to use path analysis model rather than using multiple linear regression analysis. (3) The model of this study needs to be tested on different research subjects at work where many workers are millenial generations who are found to be sedentary or alleged to have low work commitments or on jobs that have high turnover rates such as hotel employees, employees banking, hospital employees.